If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 5 + -6(x + 1) = 7x + 3 Reorder the terms: 8x + 5 + -6(1 + x) = 7x + 3 8x + 5 + (1 * -6 + x * -6) = 7x + 3 8x + 5 + (-6 + -6x) = 7x + 3 Reorder the terms: 5 + -6 + 8x + -6x = 7x + 3 Combine like terms: 5 + -6 = -1 -1 + 8x + -6x = 7x + 3 Combine like terms: 8x + -6x = 2x -1 + 2x = 7x + 3 Reorder the terms: -1 + 2x = 3 + 7x Solving -1 + 2x = 3 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -1 + 2x + -7x = 3 + 7x + -7x Combine like terms: 2x + -7x = -5x -1 + -5x = 3 + 7x + -7x Combine like terms: 7x + -7x = 0 -1 + -5x = 3 + 0 -1 + -5x = 3 Add '1' to each side of the equation. -1 + 1 + -5x = 3 + 1 Combine like terms: -1 + 1 = 0 0 + -5x = 3 + 1 -5x = 3 + 1 Combine like terms: 3 + 1 = 4 -5x = 4 Divide each side by '-5'. x = -0.8 Simplifying x = -0.8
| 2y+3(y-9)=-3(3y-18)-y | | -7(1+3x)=161 | | 1=5p-2-2 | | (c)8-10=3c+5 | | 5-[2(-4)-1]=10-x | | 2x+20=46 | | -212=-2-6(5v-2) | | 3(4-7)=-21+12z | | 5-[(-4)-1]=10-x | | x^3+2x^3=72 | | v^2-16-6v=0 | | -4y-1(5y+6)=-7y+3 | | -2(8n+1)-4(n+5)=-2 | | 2/3(3x-9)=1/4(4x-12) | | 13r-8-12= | | 10x+5+8=12x-3x+8 | | 9=4x-x | | 6(1-2m)-4(m+1)=50 | | v=x(19-2x)(8.5-2x) | | 600=4x+8x | | 600=4x*8x | | -143=-11*x | | -6(5-7r)+4(-4r-5)=28 | | 15x-3-4x=21x-8-25 | | 4(x)-4(2x)=600 | | 3x+5x-5=2(4x+1) | | -9+4r=4t-3-6 | | 3x^3-4x^2+9x-12=0 | | 1+4x+8x=-11 | | -17*x=-204 | | (x+3)/5=(3x+1)/4 | | 12x+1=12x-6 |